Variations in the Density and Distribution of Cajal Like Cells Associated With the Pathogenesis of Ureteropelvic Junction Obstruction: A Systematic Review and Meta-Analysis - Samaranayake, U. M. J. E.; Mathangasinghe, Y.; Liyanage, U. A.; de Silva, M. V. C.; Samarasinghe, M. C.; Abeygunasekera, S.; Lamahewage, A. K.; Malalasekera, A. P. (Frontiers in Surgery, 2021)
Introduction: Cajal like cells (CLCs) in the upper urinary tract have an ability to generate coordinated spontaneous action potentials and are hypothesized to help propel urine from renal pelvis into the ureter. The objective of this review was to describe the variations in the density and distribution of CLCs associated with ureteropelvic junction obstruction (UPJO). Materials and methods: Studies comparing the density and distribution of CLCs in the human upper urinary tract in patients with UPJO and healthy controls were included in this systematic review. We searched online electronic databases; Ovid MEDLINE, Scopus, PubMed and Cochrane reviews for the studies published before October 31, 2020. A meta-analysis was conducted to compare the density of CLCs at the ureteropelvic junction (UPJ) in patients with UPJO and matched controls. Results: We included 20 and seven studies in the qualitative and quantitative synthesis, respectively. In majority (55%) CLCs were located between the muscle layers of the upper urinary tract. The CLC density in the UPJ gradually increased with aging in both healthy subjects and patients with UPJO. The pooled analysis revealed that the density of CLCs at the UPJ was significantly low in patients with UPJO compared to the controls (SMD=-3.00,95%CI=-3.89 to -2.11,p<0.01). Conclusions: The reduction in CLC density at the UPJ in patients with UPJO suggests a contribution from CLCs in the pathogenesis of UPJO. Since age positively correlates with CLC density, it is imperative to carefully match age when conducting case control studies comparing the CLC density and distribution. Protocol registration number: CRD42020219882